Comparison of External Costs in Multimodal Container Transport Chain - Kos, Serđo; Vukić, Luka; Brčić, David (Promet - Traffic&Transportation, 2017)
The proposed paper discusses multimodal container transport due to savings in external costs. Relevant data have been analysed by reviewing previous research and published works for making a synthesis of one’s own conclusions. The research findings showed that there is no significant difference in the share of external costs of container transport and transport of other types of cargo in great European seaports as well as in energy consumption of multimodal rail-inland ship container transport and the same transport mode of bulk cargo. Intermodal terminals have also their own external costs. In spite of a double railway operational cost, it is important to include the railway in the intermodal terminal. The inland waterway transport has much higher external costs than sea transport. Multimodal container transport does not necessarily lower external costs. The savings are more common if the location and type of intermodal terminal are selected properly, and the sea transportation is involved in the multimodal transport chain.